ORAL HYGIENE INDEX-SIMPLIFIED MENTAL DISORDER PATIENTS IN SAMBANG LIHUM MENTAL HOSPITAL - Juli Harnida Purwaningayu; Farida Farida Auliyani; Ramadhani Fitria Nisa; Ghina Ghina Rahmatika; Norhasanah Norhasanah Norhasanah (Dentino: Jurnal Kedokteran Gigi, 2024)
Background : Oral hygiene is a risk factor for oral health, especially for individuals with mental disorders. Based on r iskesdas (2018), dental and oral health problems among the Indonesians are increased from 25.9% to 57.6%. Oral Hygiene Index Simplified (OHI-S) is a clinical tool used to measure oral hygiene status. WHO declares approximately 24 million people worldwide suffer from schizophrenia, 35 millions are affected by depression, 60 millions have bipolar disorder, and 47.5 millions have dementia[1][9] . Riskesdas shows mental disorders percentage increased from 1.7% in 2013 to 7% in 2018. Purpose : Discover the oral hygiene status of psychiatric patients through the Oral Hygiene Index-Simplified (OHI-S) in the inpatient ward of Sambang Lihum Mental Hospital. Methods : This study is a quantitative descriptive using a cross-sectional design, the purposive sampling has been carried out based on inclusion and exclusion criteria. The total sample for this study is 54 individuals. Results: 29 people (53.70%) of the patients examined had a poor OHIS category. T he OHIS of mental patients is poor in all age categories, men OHIS score is 3.2 (poor) while women OHIS score is 2.7 (fair). OHIS score for mental patients is 3.10 in total, which means in the poor category . Conclusions: OHIS measurement of mental patients at Sambang Lihum Mental Hospital is poor.